BEHAVIOURAL FINANCE: HOW PSYCHOLOGY INFLUENCES INVESTMENT DECISIONS - Rahul Sharma, Anjum Aggarwal (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
Behavioural finance is an emerging science that integrates psychological understanding with an investigation of financial decision-making. Conventional financial theories usually assume that investors are rational beings who base their decisions only on available data and logical reasoning. Behavioural finance contradicts this notion by stressing how psychological biases and emotional responses can lead to irrational and wasteful investment decisions. Overconfidence, loss aversion, swarming tendency, and mental accounting are all important psychological qualities that influence investment activity. Overconfidence can lead purchasers to believe they know more than they do and can forecast the future more accurately than they do, resulting in excessive trading and risk-taking. Loss aversion is an idea derived from prospect theory. It explains why investors prefer avoiding losses to achieving equivalent gains. As a result, they frequently opt for overly conservative investment techniques or refuse to sell losses. When a large number of people perform the same activity, this is referred to as "herding behaviour." Buyers driving asset prices away from their true values can reduce market efficiency and trigger bubbles. Mental accounting refers to how people think about and handle money based on where it originated from or what it is intended to be used for. This can lead to poor spending and investment decisions.